Algoritmo de alto desempenho para proteção numérica de linhas de transmissão imune a oscilações de potência - Morais, Adriano Peres de (2012)
This Doctoral Thesis proposes a new methodology for transmission line protection tolerant to power swings. The algorithm developed has the ability to detect, classify and locate all fault types with and without power swings, including those that produce high values of fault resistance. In a first step, it is proposed a fault distance estimator based on the leastsquare curve fitting. The fault locator, for protection proposes, was modeled by a series R-L circuit and differential equations. In a second step, the main causes and consequences of power swings in transmission lines distance relays are introduced. Also in this context, techniques to minimize these effects are presented. Besides, computer simulations of power swings, with different fault scenarios, were carried out to realize comparative analyses between the methods. The results show that none of the methods is efficient in all scenarios. Hence, there is still some concern about the performance of the protection methods against power swings. In a third step, it was developed an algorithm for numerical protection in transmission lines immune to power swings. The detection and classification steps are based on Mathematical Morphology. In order to obtain a safer operation of the relay, especially in the boundaries of threshold set, a counting strategy was developed. The main innovation of the work is based on difference of behavior of the exponentially decaying component (dc component) during a fault and during a power swing. The dc component, obtained by means of morphological filter, is used as a tripping criterion. Finally, in order to evaluate the algorithm performance, tests with different fault and power swings scenarios were performed. The results show that the technique has the speed and safety required even during power swings due to the simplicity of the algorithm used in mathematical operations.